Pancreas, kidneys and ureters - Satyapal, Kapil S. (Henry Stewart Talks, 2020)
Pancreas structure, relations, ductal system, and neurovascular supply, Kidneys structure, relations, neurovascular supply, and anomalies, Ureters description, course, and neurovascular supply